Exploration of Social Networks on Cultural Resilience in the Cirebon City - Puspitasari Rochman, Gina; Agustina, Ina Helena; Fardani, Irland; Astari, Wiwin Yuli (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2023)
As happened in Cirebon City, Indonesian culture faces the challenges of technological and scientific development that can erode or enrich the culture itself. Previous studies have shown that social networks affect economic and business resilience and this study identifies how social networks affect cultural resilience. This study concludes social networks influence increasing cultural resilience through the existence of common goals, sharing knowledge and resources, and creating innovations in the arts and culture. Maintaining and preserving culture as part of the identity and capital of urban development is a common goal of the palace and the city government. These factors underlie a culture that can survive and go hand in hand with the development of technology and science. The three palaces in Cirebon City play a major role in maintaining culture. The results of this study provide lessons for other regions and enrich studies related to the influence of social networks on the resilience and development of cities.